PCK Profile of Mathematics Education Students in Practicing the Flipped Classroom Strategy - Dyastika, Patricia Agrivina; Julie, Hongki (Jurnal Pendidikan MIPA, 2023)
Abstract: This research aims to determine the planning and implementation of the flipped classroom strategy in teaching compound probability material and determine the PCK profile of Mathematics Education students in practicing the flipped classroom strategy for teaching material at the high school level. The type of research used in this research is design research and qualitative research. The data analysis technique used in this research consists of three stages, namely: data reduction, data presentation, and drawing conclusions. Based on the results of the analysis carried out, it was found that: HLT for teaching high school level mathematics material using the flipped classroom strategy consists of four phases, namely: pre-phase, namely the researcher provides information related to the activities to be carried out; independent learning phase, namely the researcher provides a learning video regarding material on the probability of multiple events; synchronous learning phase, namely the researcher provides quizzes and practice questions for discussion; and the transfer phase, namely the researcher provides a project in the form of creating teaching modules to carry out learning practices; Undergraduate students' PCK in teaching high school mathematics material uses the flipped classroom strategy, namely 33.3% of students have PCK in the high category because they are able to fulfill some of the PCK categories. Then, the percentage of students who have PCK in the medium category is 53.3% and 13.3% of students have PCK in the low category. Keywords: PCK, HLT, strategy flipped classroom Abstrak: Penelitian ini bertujuan untuk mengetahui perencanaan dan pengimplementasian strategi flipped classroom dalam membelajarakan materi peluang kejadian majemuk serta mengetahui profil PCK mahasiswa Pendidikan Matematika dalam mempraktekan strategi flipped classroom untuk membelajarkan suatu materi ditingkat SMA. Jenis penelitian yang digunakan dalam penelitian ini yaitu penelian desain dan penelitian kualitatif. Teknik analisis data yang digunakan dalam penelitian ini terdiri dari tiga tahap yaitu: reduksi data, penyajian data, dan penarikan kesimpulan. Berdasarkan hasil analisis yang dilakukan diperoleh bahwa: HLT untuk membelajarkan materi matematika tingkat SMA menggunakan strategi flipped classroom terdiri dari empat fase yaitu: pra fase yaitu peneliti memberikan informasi terkait kegiatan yang akan dilakukan; fase belajar mandiri yaitu peneliti memberikan video pembelajaran mengenai materi peluang kejadian majemuk; fase pembelajaran sinkronus yaitu peneliti memberikan kuis dan latihan soal untuk diskusi; dan fase transfer yaitu peneliti memberikan proyek berupa membuat modul ajar untuk melakukan praktik pembelajaran; PCK mahasiswa S1 dalam membelajarkan matematika materi SMA menggunakan strategi flipped classroom yaitu sebanyak 33,3% mahasiswa memiliki PCK dalam kategori tinggi karena mereka mampu memenuhi sebagaian kategori dari PCK. Kemudian, persentase mahasiswa yang memiliki PCK dalam kategori sedang sebanyak 53,3% dan 13,3% mahasiswa memiliki PCK dalam kategori rendah.  Kata kunci: PCK, HLT, strategi flipped classroom   DOI: http://dx.doi.org/10.23960/jpmipa/v24i3.pp646-657